The Concept of Hadith, Meaning, and Position of Hadith, Implementation and Comparison in Hadith Learning Application: Hadith Encyclopedia and Hadith Collection - Shinta Ilahi, Nurul Anggraeni; Nurwahidin, Nurwahidin; Izdiyan, Mohammad (UI Scholars Hub, 2023)
The rapid development of information and communication technology has added new perspectives to research on the concept of hadith, the meaning, and position of hadith, which can also be seen as an effort to improve, enforce, and preserve hadith among the Muslim community in the online realm. The results of this study identified two specific mobile applications, namely the Hadith Encyclopedia and the Hadith Collection. This research aims to test several mobile applications that can be used to speed up the learning process and show how simple the verification and authentication of a hadith is in modern times. Hadith data in both applications is collected quantitatively. This study finds that several hadith verification features are continuously being improved on these two mobile applications, including source text, hadith standings, Sanad, and daily hadith features. All the features are advantageous to learn hadith practically.